More than child's play: tackling speech anxiety among Malaysian ESL learners through gamification / Mia Emily Abdul Rahim ... [ et al.] - Abdul Rahim, Mia Emily; Abdul Rahim, Emma Marini; Razawi, Nurul Amilin; Mohamed, Nuruladilah (Universiti Teknologi MARA, Perak, 2023)
When second language learners have language anxiety especially when they are using the speaking skills, they are more likely to experience anxiety, self-doubt, frustration, and fear that will affect their ability to learn the languages. However, based on previous research, it is shown that learners' anxiety over public speaking significantly decreased when gamification was included in the classroom. Therefore, in this study, the main objective was to explore the students' perception towards the gamification setting in reducing speech anxiety among UiTM students. The study employs a quantitative study with 221 participants consisting of undergraduates from various faculties in UiTM. A descriptive analysis was used to analyze the data. From the results, it is found that most of the students experienced a level of anxiety in the beginning despite using the virtual gamification setting. However, they believe that the virtual speech application helped them in getting an improved positive experience when delivering a speech, particularly in easing their anxiousness upon speaking in front of an audience.